BENEFITS OF CAMEL PRODUCTS, USES AND INSTRUCTIONS. - Xalilova Lobar Umarovna; Saparov Kalandar Abdullayevich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Abstraсt: The article is devoted to solving problems in the reproduction of camel family enterprises distributed in this region, the number of workers, the importance of camels in medicine and industry, and measures.